A study of hybrid self-centring beam-to-beam connections equipped with shape-memory-alloy-plates and washers. (November 2022) - Yam, Michael C.H.; Ke, Ke; Huang, Yun; Zhou, Xuhong; Liu, Yicen
Abstract: This paper examined the hysteretic performance of a novel hybrid self-centring beam-to-beam connection equipped with shape memory alloy (SMA) plates and SMA Belleville washers. An experimental programme employing three proof-of-concept test specimens with varied SMA plate geometries and connection configurations was conducted. The test connections showed recentring performance with controllable residual deformations. The encouraging energy dissipation capacity of the test connections accompanied by excellent ductility was also confirmed. Subsequently, a numerical study was carried out to help interpret the test results and to further examine the connection's load carrying mechanism. In the numerical work, a hybrid finite element (FE) modelling technique enabling reproducing the residual strain development of SMA plates under hysteretic loading was developed and verified. The test and numerical study showed that the self-centring ability of the connection was appreciably affected by the hysteretic behaviour of SMA plates. The FE results also confirmed that the connection behaviour was sensitive to the connection configuration, and a minor gap between the beam segments could initiate intense buckling of the SMA plates. Nevertheless, the lateral deflection of the SMA plates can be suppressed by effective buckling restraints. To facilitate practical application, a theoretical prediction model enabling the quantification of a bilinear skeleton response of the connection was proposed, and the adequacy of the prediction model was evidenced by the correlation among the results of the tests, FE simulations and design predictions. Highlights: Beam-to-beam connections equipped with SMA plates and washers were tested. The connections showed recentring performance. A hybrid finite element modelling technique was developed. A bilinear model for quantifying the nonlinear behaviour was proposed.